Unexpected feeding behaviour inferred by DNA metabarcoding of Barents Sea skates - Kleiven, Stian K. (UiT Norges arktiske universitet, 2022)
Feeding studies give an indication about the role and position of species within ecosystems and provide crucial knowledge for management. Traditional methods are based on morphological identification of prey. DNA metabarcoding is a promising tool that allow for identification of specific prey items, also when highly digested. A total of 63 stomachs from three skate species caught in the Barents Sea region were investigated by DNA metabarcoding. Differences were found between species and size classes, reflecting the distributions and respective lengths of the skates. No sexual differences were found. The smaller size classes preferred small and soft-bodied prey species. Arctic skate have been observed to perform short-term depth changes, being confirmed by a higher portion of pelagic diet compared to the other two. Spinytail skate, reaching the largest maximum size, was more piscivorous. The smaller thorny skate predominantly preyed upon soft-bodied invertebrates. A comparison with traditional methods was performed, revealing that DNA metabarcoding identified up to twenty times more species. This includes rapidly digestible prey such as Annelida, Cnidaria and Chaetognatha, although secondary predation cannot be ruled out. DNA metabarcoding is a powerful tool for mapping the range of prey diversity and is an important complementation to traditional methods.